2002
DOI: 10.1002/hup.420
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment with both lithium and sodium valproate may normalize phosphoinositol cycle activity in bipolar patients

Abstract: These findings examine two key components of the PI-cycle in treated euthymic bipolar (myo-inositol and PME concentrations). The results from this study are consistent with the suggestion that chronic treatment with either lithium or sodium valproate in bipolar patients may normalize PI-cycle functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 36 publications
(53 reference statements)
1
44
0
3
Order By: Relevance
“…Several studies utilizing 31 P MRS suggest that euthymic BPD patients on treatment have PME concentrations that are not significantly different from healthy controls (Kato et al, 1994b(Kato et al, , 1995Murashita et al, 2000;Silverstone et al, 2002;Hamakawa et al, 2004), although other studies did find reduced concentrations (Kato et al, 1993(Kato et al, , 1994a.…”
Section: Euthymic Patientsmentioning
confidence: 96%
“…Several studies utilizing 31 P MRS suggest that euthymic BPD patients on treatment have PME concentrations that are not significantly different from healthy controls (Kato et al, 1994b(Kato et al, , 1995Murashita et al, 2000;Silverstone et al, 2002;Hamakawa et al, 2004), although other studies did find reduced concentrations (Kato et al, 1993(Kato et al, , 1994a.…”
Section: Euthymic Patientsmentioning
confidence: 96%
“…The majority show results consistent with decreased myo-inositol or increased InsP 1 , [74][75][76][77][78] however, some find no difference. 79,80 The failure to find differences in chronically treated patients has been interpreted as treatment leading to normalization of signaling. Changes may also reflect spatial heterogeneity in Li þ and VPA responses, and a recent study found inositol reduced by Li þ in white matter, but increased in grey matter.…”
Section: Preclinical and Clinical Studiesmentioning
confidence: 99%
“…However, this study is limited by most of the patients receiving concomitant medications, confounding interpretation of results. In contrast, other studies report no change in cortical [35,36] or anterior cingulate [37] mI in euthymic bipolar patients treated with lithium compared with healthy control subjects. The finding of reduction in mI has not been observed in healthy subjects after lithium administration and seems to be specific to patients with bipolar disorder [38].…”
Section: Myo-inositolmentioning
confidence: 62%